Effects of deliberate practice and self-efficacy on clinical skills performance in a fundamental nursing course - Erik Kusuma; Syaifuddin Kurnianto; Eko Prasetya Widianto; Mareta Deka Paraswati; Suhendra Agung Wibowo (Nursing and Health Sciences Journal (NHSJ), 2026)
Clinical skill deficits among vocational nursing students compromise patient safety, particularly when conventional training lacks structured feedback mechanisms. This study investigated the effects of a deliberate practice intervention and self-efficacy on clinical skills performance. A quasi-experimental pretest–posttest control-group design was conducted with 60 second-semester diploma nursing students, who were allocated via matched sampling to the experimental (n=30) or control (n=30) groups. The experimental cohort completed an eight-session deliberate practice program (90 minutes per week for four weeks), while the control group received standard instruction. Blinded assessors evaluated psychomotor skills using a validated Objective Structured Clinical Examination checklist, and self-efficacy was measured with the General Self-Efficacy Scale. Intervention fidelity was rigorously maintained through protocol checklists. The experimental group demonstrated significantly superior post-intervention clinical skills scores compared to controls (mean difference = 12.47, 95% CI [8.40, 15.60], p < .001). Self-efficacy independently predicted skill performance (β = 0.29, p = .008). Combined, the intervention and self-efficacy explained 58.3% of the variance in clinical performance (adjusted R² = 0.55, p < .001). Structured deliberate practice substantially enhances clinical competency in vocational nursing students, with self-efficacy functioning as a critical complementary predictor. Nursing educators should systematically integrate deliberate practice frameworks with targeted confidence-building strategies to optimize psychomotor skill acquisition and strengthen patient safety outcomes.